Combining KAOS and GHENeSys in the requirement and analysis of service manufacturing. Issue 3 (2015) - Silva, Javier Martinez; Silva, José Reinaldo
Abstract: The design of planning problems has demanded more attention from the academy - which looks for new approaches - and from practitioners - which seeks for new and better results for real applications. AI approaches have been used for different applications in many domains, including manufacturing, and specially manufacturing services. However, as in all domains, a design process has to be provided to the planning (and scheduling) design to get all advantages in the use of heuristic or analytic methods. Requirements analysis is a key issue for that design process and needs to be enhanced to fit users and stakeholder expectations. In this work we focus on requirements analysis for planning problems using Petri Nets derived from a UML representation of requirements. A transference algorithm is proposed to synthesize a Petri Net from KAOS diagram and allow analysis using Petri Net property analysis suitable to be applied to large projects.